The Concept of Interrelation of Giving and Taking a Bribe - Михайленко Дмитро Григорович; Mychailenko D.G. (My University, 2012)
In this article the author analyzes the existing images concerning with a parity of a giving and taking the bribe. It is proved that the bribery is a uniform difficult bilateral crime which consists of two necessary interconnected elements: giving and taking the bribe. This two elements are necessity co-authors of the crime.
Mychailenko D. G. The Concept of Interrelation of Giving and Taking a Bribe / D. G. Mychailenko // Proceeding of Turkey-Ukraine Comparative Criminal Law Symposium - II «Legat Policy of EU Countries: Compapative Aspecfs»; 28-29.08.2012. – Odessa/Ukraine: NUOLA, 2012. – P. 263-277.
Keywords: хабарництво; давання хабара; одержання хабара; взяточничество; дача взятки; получение взятки; bribery; giving of the bribe; taking of the bribe